Produção de olefinas leves a partir de etanol em ZSM-5 sintetizada sem direcionador nitrogenado - Albiero, Jalusa Konzen (2015)
The petrochemical industry is currently strongly based on the production of light olefins ethylene and propylene, which are mainly produced by hydrocarbons from oil. Due to the environmental appeal and unstable oil market scenario, alternative routes to the production of these olefins are being developed, meanly regarding the use of alcohol as raw material. In this context, ethanol is highlighted with Ethanol to Olefins Process (ETO), in which there is catalytic conversion via reactions of dehydration, oligomerization, cracking, isomerization, among others. This work aims to obtain ethylene and propylene from ethanol using ZSM-5 zeolite as catalyst in its acid form. The synthesis of this material was performed using non-conventional sources of silicon and aluminum, kaolin and silica extracted from rice husk ash, and in the absence of nitrogenous templates. The use of seeds was employed together with ethanol, which acts as cotemplate of the zeolitic structure, in different quantities, and in different silica/alumina ratios and crystallisation times. The influence of each of these variables was evaluated with the support of a full factorial experimental design on the final characteristics of the synthesized samples, such as relative crystallinity, chemical composition and textural properties. All samples presented the characteristic crystal structure of ZSM-5 as verified by both X-ray diffractograms and infrared spectra. However, samples with small amounts of seed and ethanol added to short periods of crystallization presented lower crystallinities and specific areas in comparison to other samples. On the other hand, the use of high quantities of seed can lead to the formation of quartz when the crystallization time is extended. With the catalytic tests of ethanol conversion into olefins it was possible to evaluate the influence of synthesis variables, the residence time and the concentration of ethanol in feed, proving the importance of all synthesis variables in the distribution of the reaction products The total conversion of ethanol was observed in all tests made, evidencing the high activity of hZSM-5 in the dehydration of ethanol to ethylene, being the propylene yield strongly influenced by the reaction temperature and characteristics of the catalitic material, with a maximum yield of 27% at 500 °C. The HZSM-5 presented high stability under reaction conditions while maintaining the production of ethylene for more than 40 hours of reaction, whereas the coke formation drastically reduces the production of propylene still in the early hours of reaction.